Cells with stem‐like properties are associated with the development of HPV18‐positive cervical cancer. Issue 3 (9th December 2022) - Kusakabe, Misako; Taguchi, Ayumi; Tanikawa, Michihiro; Wagatsuma, Ryota; Yamazaki, Miki; Tsuchimochi, Saki; Toyohara, Yusuke; Kawata, Akira; Baba, Satoshi; Ueno, Toshihide; Sone, Kenbun; Mori‐Uchino, Mayuyo; et al.
Abstract: The cellular origins of cervical cancer and the histological differentiation of human papillomavirus (HPV)‐infected cells remain unexplained. To gain new insights into the carcinogenesis and histological differentiation of HPV‐associated cervical cancer, we focused on cervical cancer with mixed histological types. We conducted genomic and transcriptomic analyses of cervical cancers with mixed histological types. The commonality of the cellular origins of these cancers was inferred using phylogenetic analysis and by assessing the HPV integration sites. Carcinogenesis was estimated by analyzing human gene expression profiles in different histological types. Among 42 cervical cancers with known HPV types, mixed histological types were detected in four cases, and three of them were HPV18‐positive. Phylogenetic analysis of these three cases revealed that the different histological types had a common cell of origin. Moreover, the HPV‐derived transcriptome and HPV integration sites were common among different histological types, suggesting that HPV integration could occur before differentiation into each histological type. Human gene expression profiles indicated that HPV18‐positive cancer retained immunologically cold components with stem cell properties. Mixed cervical cancer has a common cellular origin among different histological types, and progenitor cells with stem‐like properties may be associated with the development of HPV18‐positive cervical cancer. Abstract : To gain new insights into the carcinogenesis and histological differentiation of human papillomavirus (HPV)‐associated cervical cancer, we conducted genomic and transcriptomic analyses of cervical cancer with mixed histological types. The results suggest that mixed cervical cancer has a common cellular origin among different histological types, and progenitor cells with stem‐like properties may be associated with the development of HPV18‐positive cervical cancer. In addition, cells with stem‐like properties are immunologically cold.